Psychopathological Symptom Load and Distinguishable Cerebral Blood Flow Velocity Patterns in Patients With Schizophrenia and Healthy Controls: A Functional Transcranial Doppler Study - Egger, Stephan T.; Bobes, Julio; Rauen, Katrin; Seifritz, Erich; Vetter, Stefan; Schuepbach, Daniel (Frontiers in Psychiatry, 2021)
Introduction: Schizophrenia is a severe psychiatric disorder, with executive functions playing a pivotal role for the course of the disease. Neurocognitive impairment, and deficits in executive functioning seem are related to alterations in cerebral blood flow. We aim to study the effects of symptom load on brain hemodynamics. Methodology Thirty patients with schizophrenia and 15 healthy participated. Symptoms of Schizophrenia were measured with the Brief Psychiatric Rating Scale (BPRS); patients were divided in two groups according to their symptom load. We examined cerebral blood flow velocity during the Trail Making Tests (TMT) using functional Transcranial Doppler (fTCD). Continuous data were analyzed using the general additional model (GAM) with a univariate analysis of variance (ANOVA) for group comparisons. Results Patients and control subjects were comparable regarding, age, sex and years of parent`s education. In comparison to healthy controls, symptom load positively correlated with the time to complete the TMTs. Patients showed with increasing symptom load different hemodynamic profiles than healthy controls in the TMT- A (F (6,1792) = 17, p<0.000); and in the TMT-B (F (6, 2692) = 61.93, p<0.000). Conclusions Patients with schizophrenia performed less satisfactorily on both TMTs. The performance deteriorated with increasing symptom load, parallel with a distinct cerebral blood flow pattern in the MCA. Our results further support the view that schizophrenia, particularly symptom load, influences the performance of neurocognitive tasks: while being related to distinct brain hemodynamic patterns.